1996
DOI: 10.1086/309854
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Hard X-Ray Plerion in the Candidate Historical Remnant G11.2−0.3

Abstract: We present the results of a 32 ks Advanced Satellite f or Cosmolog y and Astroph ysics (ASCA) observation of G11.2Ϫ0.3, which is by far the strongest candidate for the remnant of the historical supernova SN 386. A center-brightened, hard, nonthermal X-ray source was found within the remnant, which we interpret to be plerionic emission due to an embedded pulsar. Our observations indicate that the remnant is a member of the class of ''composite'' remnants, as was hinted by previous observations. The central emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 18 publications
4
36
0
Order By: Relevance
“…The derived age (a few thousand years) and the presence of a central X-ray source makes 3C 397 similar to the young SNRs G11.2È0.3 (Vasisht et al 1996), Kes 73 , and RCW 103 (Petre & Gotthelf 1998). G11.2[0.3 harbors a hard X-ray plerion powered by a fast millisecond pulsar (Torii et al 1997).…”
Section: Discussionmentioning
confidence: 64%
“…The derived age (a few thousand years) and the presence of a central X-ray source makes 3C 397 similar to the young SNRs G11.2È0.3 (Vasisht et al 1996), Kes 73 , and RCW 103 (Petre & Gotthelf 1998). G11.2[0.3 harbors a hard X-ray plerion powered by a fast millisecond pulsar (Torii et al 1997).…”
Section: Discussionmentioning
confidence: 64%
“…The PWN and 65-ms period pulsar associated with G11.2−0.3 were discovered using ASCA observations (Vasisht et al 1996;Torii et al 1997), and Kaspi et al (2001) showed that the pulsar is only 8 from the geometric center of the SNR. Borkowski et al (2016) used multiple epochs of Chandra observations to measure a shell expansion rate that implied an age of 1400-2400 years, making G11.2−0.3 one of the youngest identified CC SNRs in the Milky Way.…”
Section: Properties Of the Snrsmentioning
confidence: 99%
“…The first hints of a central plerionic component came from high-frequency, single-dish radio measurements that suggested a central flattening of the radio spectrum (Morsi & Reich 1987). ASCA observations first clearly demonstrated that there was a central, nonthermal X-ray source (Vasisht et al 1996). This component was resolved by Chandra, the image of which has been presented in Paper I.…”
Section: Introductionmentioning
confidence: 98%